Genetically instrumented circulating metabolites and hepatobiliary cancer risk: A multi-tiered Mendelian randomization and functional interrogation - Tuo, Lin; Yan, Li Ting; Liu, Ying; Wang, Shu Qiang; Yang, Xing Xiang; An, Xiang (Frontiers in Oncology, 2025)
BackgroundHepatobiliary malignancies—including hepatocellular carcinoma and cholangiocarcinoma—are major causes of cancer-related mortality worldwide, yet their regulatory pathways remain incompletely defined.MethodsWe employed a two-sample Mendelian randomization (MR) approach to systematically investigate causal relationships between 1,400 serum metabolites and hepatobiliary cancer risk. Through stringent quality control (all SNPs with F-statistics > 10) and sensitivity analyses (MR-Egger regression, weighted median method, and MR-PRESSO), we identified 10 candidate metabolites.ResultsMeta-analysis confirmed three metabolites with robust associations: risk-increasing dimethylarginine (SDMA+ADMA) and 4-hydroxyhippurate, and protective 3-hydroxyisobutyrate. Multivariable MR validated the independent effects of 4-hydroxyhippurate and 3-hydroxyisobutyrate. In vitro functional experiments demonstrated that 4-hydroxyhippurate promoted, whereas 3-hydroxyisobutyrate inhibited, hepatocellular carcinoma cell proliferation.ConclusionThese findings advance understanding of metabolic dysregulation in hepatobiliary malignancies and nominate candidate diagnostic biomarkers and therapeutic targets, providing translationally relevant hypotheses for precision medicine.